ANALISIS KESESUAIAN LAHAN UNTUK USAHA GARAM INDUSTRI DI WILAYAH PESISIR KABUPATEN PANGKAJENE DAN KEPULAUAN - Mustakim Mustakim; Muh Kasnir; Abdul Rauf (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2019)
The purpose of this study is to find suitable pond areas for salt ponds. Modeling in GIS, site selection studies are appropriate for industrial salt farms. Geographic Information System modeling can predict ponds that are appropriate and not appropriate for industrial salt ponds. The model used in this study is the index model. In Suharyadi and Danoedoro (2004) explained that index modeling involves the use of scores for each different category. this model can be applied to GIS Vector or raster. Overlaying maps involves arithmetic calculation processes, either amount, subtraction, multiplication or division. The index or score possessed by the new mapping unit on the derived map illustrates the combined conditions of various criteria used as the basis for decision making. The results of the analysis found that the area that was very suitable for salt ponds reached 1716.58 ha or 81.97% of the area of ponds in Pangkep Regency. Areas that are not suitable for salt ponds reach 377.48 ha or reach 18.03%. from pond area. . Fishponds suitable for industrial salt farms are found in areas close to the coastline